Strategi Pemasaran Usaha Mikro Kecil Menengah pada Era Digital di Kota Makassar - Ellyana Haris, Andi Tenri; Tahir, Rahmawati; Putri Lanrang Haris, Andi Tenri Lawa; Gunawan, Muhammad Taufan (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
This study aims to analyze and enhance digital-based product marketing strategies for MSME actors in Makassar City. This research adopts a case study approach focusing on the Mom To Mom (MTM) Mompreneur Community in Makassar. The study was conducted over a two-month period, from April to May 2024. The sampling technique employed was purposive sampling, involving 37 MSME actors operating in the culinary, fashion, services, and other sectors. Data analysis was carried out using SWOT analysis. The findings indicate that the effective and sustainable utilization of digital technology as a medium for promotion and marketing enables MSME products to gain greater market recognition, thereby increasing sales. Furthermore, the creation of high-quality, creative, and innovative promotional content on a consistent basis also contributes to attracting customer interest, expanding market reach, boosting sales, and ensuring long-term business stability. MSME actors need to remain adaptive to technological advancements as an integral part of their product marketing strategies.